De l’hybridité du corps dans l’art marocain - Anouar Ouyachchi (Itinéraires)
In the Arab-Muslim societies, the body often calls the notion of self-government. Caught in the sphere of the sacred Muslim, it is often the subject of discourses that mark the limits of possible behaviors. In Morocco, artistic representations of the body not only aim to translate the repression suffered by the latter, but also to take away the sacred aura of it. Through the notion of hybridity, we will question in this article the work of a few artists, in order to show how the Moroccan art invests the body as an instrument of quest and identity negotiation beyond the essentialist dichotomies.